Reduced interleukin‐2 responsiveness impairs the ability of Treg cells to compete for IL‐2 in nonobese diabetic mice. Issue 5 (9th February 2016) - James, Cini R; Buckle, Irina; Muscate, Franziska; Otsuka, Masayuki; Nakao, Mari; Oon, Jack SH; Steptoe, Raymond J; Thomas, Ranjeny; Hamilton‐Williams, Emma E
Abstract : Enhancement of regulatory T cell (Treg cell) frequency and function is the goal of many therapeutic strategies aimed at treating type 1 diabetes (T1D). The interleukin‐2 (IL‐2) pathway, which has been strongly implicated in T1D susceptibility in both humans and mice, is a master regulator of Treg cell homeostasis and function. We investigated how IL‐2 pathway defects impact Treg cells in T1D‐susceptible nonobese diabetic (NOD) mice in comparison with protected C57BL/6 and NOD congenic mice. NOD Treg cells were reduced in frequency specifically in the lymph nodes and expressed lower levels of CD25 and CD39/CD73 immunosuppressive molecules. In the spleen and blood, Treg cell frequency was preserved through expansion of CD25 low, effector phenotype Treg cells. Reduced CD25 expression led to decreased IL‐2 signaling in NOD Treg cells. In vivo, treatment with IL‐2–anti‐IL‐2 antibody complexes led to effective upregulation of suppressive molecules on NOD Treg cells in the spleen and blood, but had reduced efficacy on lymph node Treg cells. In contrast, NOD CD8 + and CD4 + effector T cells were not impaired in their response to IL‐2 therapy. We conclude that NOD Treg cells have an impaired responsiveness to IL‐2 that reduces their ability to compete for a limited supply of IL‐2.